Deconstructing Modern Educational Theories: Reclaiming Transcendental Values in Islamic Education Curriculum - Ahmad Silmul Fuady; Muhammad Amir Kulal (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
An increasingly pervasive educational paradox lies in the capacity of modern educational theories to generate technical competence while simultaneously eroding the ontological and epistemological foundations that give human learning its ultimate meaning. Beneath the dominance of progressivism, constructivism, and outcome-based educational frameworks resides a secular architecture that progressively marginalizes transcendental sources of knowledge and redefines educational success through empirical utility and socio-economic functionality. This article undertakes a qualitative philosophical-conceptual inquiry employing text-based hermeneutics and critical content analysis of a corpus comprising foundational Western educational theories and seminal works of Islamic educational philosophy. The analysis reveals a structural cascade through which revelation, metaphysical consciousness, and sacred values are displaced from the center of curriculum design and subsequently translated into measurable behavioral indicators, reducing transcendental realities such as ikhlas, taqwa, and spiritual awareness to functional assessment categories. Such reductionism exposes a profound ontological mismatch between secular educational paradigms and the epistemological foundations of Islamic education. In response, the study advances a transcendental canopy model that repositions Divine Revelation (Wahyu) as the supreme epistemological framework governing all domains of knowledge. This reconstruction offers a philosophical foundation for curriculum renewal, educational leadership transformation, and the intellectual de-secularization of contemporary Islamic education